Soil and plant factors associated with iron chlorosis of Kentucky bluegrass - Harívandí, Mohammad Ali., author; Butler, J. D., advisor; Soltanpour, P. N., committee member; Workman, M., committee member (Colorado State University. Libraries, 1975)
Iron (Fe) chlorosis is a common problem on turfgrasses grown under alkaline soil conditions. The objective of this study was to determine the iron uptake efficiency of different varieties of Kentucky bluegrass. In this study, 25 varieties and 5 blends of Kentucky bluegrass (Poa pratensis L.) were utilized. Maintenance practices for all varieties were the same, and at the time of sampling the grasses were three years old, were well established, and had not been treated with iron containing materials. Soil pH, soil available iron, plant total iron, plant chlorophyll content, and plant iron uptake efficiency were determined. Also, the visual appearance of the turf was scored before sampling. Statistical treatment indicated significant differences in the total iron and chlorophyll content of the varieties. The following significant correlations were observed: (1) soil available iron to iron uptake efficiency (negative); (2) plant total iron to iron uptake efficiency (positive); (3) plant chlorophyll content to plant iron content (positive); (4) plant chlorophyll content to iron uptake efficiency (positive). The varieties and blends were significantly different in their iron uptake efficiency.
Covers not scanned.
Keywords: Kentucky bluegrass; Soils -- Iron content